How is Contact Force implemented in routine clinical practice? Results from a French National and Monaco Survey. Issue 2 (15th February 2019) - Bun, Sok‐Sithikun; Lațcu, Decebal Gabriel; Taghji, Philippe; Anselme, Frederic; Boveda, Serge; Cebron, Jean‐Pierre; Defaye, Pascal; Deharo, Jean‐Claude; Fauchier, Laurent; Gandjbakhch, Estelle; Gras, Daniel; Klug, Didier; et al.
Abstract: Background: Combination of elementary parameters (force, time, power, impedance drop) has been proposed to optimize radiofrequency (RF) delivery. They have been partially validated in clinical studies. Aims: The aim of this study was to assess contact‐force (CF) implementation into clinical practice. Methods: A 36‐question electronic form was sent to 105 electrophysiologists (EP) including some general questions concerning the practice of catheter atrial fibrillation ablation and items concerning the parameters used for CF‐guided ablation. Results: Answers from 98 EP were collected (93% response rate). The CF‐catheters used were Smart Touch, Biosense (52%), Tacticath, Saint‐Jude Medical (12%), or both (27%) and no CF (9%). The power applied on the left atrial (LA) anterior (LAAW) and posterior (LAPW) wall was, respectively, 26‐34 W (for 73% of the EP) and below 25 W (88% of the EP). Forty percent of the Visitag ® users mostly used the nominal parameters. Seventy‐five percent of the users did not use automatic display of the impedance drop. For the Tacticath users, 57% used a target value of 400 gs on the LAAW and 300 to 400 gs on the LAPW. Lesion Size Index was exceptionally used. Conclusions: The parameters used for CF‐guided ablation are widely variable among the different operators. Further prospective studies are needed to validate the targets for automatic annotation of the RF applications.